HUBUNGAN ANTARA SELF REGULATED LEARNING DENGAN STRES AKADEMIK PADA SISWA KELAS XI SMA NEGERI X TULUNGAGUNG DENGAN SISTEM FULL DAY SCHOOL - PRISKILA, VENNA; INA SAVIRA, SITI (Character Jurnal Penelitian Psikologi, 2019)
Abstrak Penelitian ini bertujuan untuk menguji hubungan antara self regulated learning dengan stres akademik pada siswa kelas XI di SMA Negeri X Tulungagung dengan sistem full day school. Metode yang digunakan dalam penelitian ini adalah kuantitatif. Penelitian ini menggunakan subjek berjumah 210 siswa di SMA X Tulungagung. Instrumen penelitian ini ialah menggunakan skala self regulated learning dan stres akademik. Penelitian ini menggunakan analisis data product moment. Hasil dari analisis data menunjukkan koefisien korelasi sebesar - 0,485 dengan taraf signifikansi 0,000 (p<0,05) yang berarti semakin tinggi self regulated learning siswa maka semakin rendah stres akademik siswa dan sebaliknya jika semakin rendah self regulated learning siswa maka semakin tinggi stres akademik pada siswa. Kata Kunci : Self regulated learning, stres akademik, siswa, full day school. Abstract The purpose of this research was to examine the relationship between self regulated learnig and academic stress on student of senior high School X Tulungagung. This research used quantitative research methods. Subject in this research were 210 students of senior high school X Tulungagung. The data were collected using learning family functioning scale and emotion regulation scale. The data were analysed using product moment correlation. The results showed the value of correlation coefficient of -0,485 with a probability level of 0,0`00 (p<0,05). It can be concluded that there is a significant relation between self regulated learning with academic stress on students of privat senior high school X Tulungagung which mean that the higher the self regulated learning, the lower the academic stres and the lower self regulated learning the higher academic stres on students. Keywords : Self regulated learning, academic stress,students, full day school.